Effective Communication Strategy with Community and Landowner in the Construction of High Voltage Power Transmission Line in Peninsular Malaysia - Mei Ye, Kho; Mohd Danuri, Mohd Suhaimi; Mohamed, Othman; Selamat, Nor Eliza (Journal of Surveying, Construction and Property, 2017)
Power transmission system has been designed as an overhead lines constructed with lattice towers or monopoles; or as underground cables to transmit electricity supply from power plant to consumers. In order to meet the incremental demand of power supply, transmission networks require upgrading works and the construction of more overhead tower or monopole. This paper presents the implication of the community and landowner concerns on the effects of high voltage power transmission overhead lines construction in Peninsular Malaysia. Quantitative approach was applied in this research by distributing questionnaires survey to the targetted respondents. Language, culture, perception, knowledge and other factors such as political influence were significance variables which can affect effective communication strategy in the construction of high voltage power transmission lines in Peninsular Malaysia. Therefore, it is important to have an effective communication between all parties to generate positive outcome in supporting the progressive construction of the high voltage power transmission overhead lines.